A novel integrated modeling approach for filter diagnosis in gas turbine air intake system. (May 2022) - Jin, Yunfeng; Liu, Chao; Tian, Xin; Huang, Haizhou; Deng, Gaofeng; Guan, Yunlong; Jiang, Dongxiang
Due to the complex and harsh environmental factors, the useful life of the filter in the gas turbine air intake system is usually less than its design life. When the filter is seriously degraded, the power and thermal efficiency of the gas turbine will decrease obviously due to the increase of inlet pressure loss. For evaluating the health condition of filters in the air intake system, this work forms a filter pressure loss model with the defined health index for the filter and five external environmental and control factors. By integrating the gas path component model, the combined model is applied in a real data set and the results show that (i) the proposed health index is efficient in representing the degradation state of the filter, (ii) the influencing factors on the pressure loss are successfully decoupled and their contributions on the pressure are quantitatively estimated, and (iii) the integrated model of filter pressure loss and gas path component can be used to better estimate the deterioration states of the filter as well as the gas turbine performance.